(untitled) (Altre Modernità, 2011)
Cecil B. DeMille adapted for the screen the biblical text of Exodus twice, and in both cases he devised sophisticated strategies for intersemiotic translation with the aim to create a great show for a popular Christian audience. This is the reason why The Ten Commandments cannot be considered a mere illustration of the biblical story but instead a complex fiction film, which uses the Bible only as a starting point.